Rice Farming Productivity Amid Seasonal Changes: A Case Study of Kaloling Village, Sinjai - Megawati; Fadilah Nurdin; Ahfandi Ahmad; Nilmalasari; Risma Niswati Tarman (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2026)
Seasonal variability has become a major constraint for rice farming in rainfed and simple-irrigated areas. This study aimed to analyze the effect of seasonal changes on rice farming productivity in Kaloling Village, East Sinjai District, Sinjai Regency. Seasonal change was measured using three indicators: planting time shift, water availability condition, and increasing pest attack, while productivity was measured through land, labor, capital, technology adoption, and planting intensity indicators. The study employed a quantitative descriptive-associative approach. The population consisted of 411 members of 12 farmer groups, and 41 respondents were selected using proportionate sampling. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed using multiple linear regression. The results showed that planting time shift had a negative and significant effect on rice farming productivity (t = -7.723; p < 0.001), water availability condition had a positive and significant effect and became the dominant factor (t = 8.086; p < 0.001), and increasing pest attack had a negative and significant effect (t = -2.203; p = 0.034). Simultaneously, the three variables significantly affected rice farming productivity (F = 23.444; p < 0.001), with an R-square value of 0.655. These findings indicate that adaptive strategies should prioritize water management, synchronized planting calendars, and integrated pest control to sustain rice productivity under seasonal uncertainty.